Evaluating South Korean Based Mobile Role Playing Games with Playability Heuristic Evaluation - Laja Uggah, Louis; Azaini bin Abdul Manaf, Ahmad; Azizi Abdul Adis, Azaze (International Journal of Engineering and Technology, 2018)
This research compared two role-playing games developed by South Korean-based company which is Netmarble Games. These games were selected based on their number of downloads among iOs mobile users. The Heuristic Evaluation method was selected to study this games based on 3 categories which are Mobility, Usability and Gameplay. In conclusion, this study has presented evaluation on these 2 games based on playability heuristic evaluation and have identified key areas to be improved by game designers.Â Â